Exploring high-performance integration in a plastic crystal/film with switching and semiconducting behavior. Issue 5 (7th February 2020) - Zhang, Zhi-Xu; Zhang, Tie; Shi, Ping-Ping; Zhang, Wan-Ying; Ye, Qiong; Fu, Da-Wei
Abstract : As a room-temperature plastic crystal, ( N, N -dimethylpiperidinium)3 Bi2 Cl9 can integrate semiconducting behavior and switchable properties into one single flexible material, making it a potential candidate in flexible multifunctional devices. Abstract : Multifunctional materials enable the integration of multiple physical signals in a single device for seamless integration, offering new opportunities in areas such as modern smart devices. For the needs of flexible devices, molecular functional materials are highly preferred due to their structural tunability, environmental friendliness and easy film formation. However, designing such multifunctional materials suitable for thin film devices has always been a huge challenge, especially semiconducting switchable dielectrics. Considering the unique structural properties and mechanical flexibility of plastic crystals, we have successfully designed an excellent multifunctional material, ( N, N -dimethylpiperidinium)3 Bi2 Cl9, which shows outstanding dielectric switching and semiconducting behavior comparable to ZnO. The plastic phase transition below room temperature and multiaxial characteristics caused by structural variation give its thin film preferred structural flexibility, good uniformity and stability. These attributes make it a potential candidate in flexible multifunctional devices, realizing the high-performance integration of semiconducting and switchable properties.